Surface Octahedral Distortions and Atomic Design of Perovskite Interfaces. (28th June 2013) - Petrov, A. Yu.; Torrelles, X.; Verna, A.; Xu, H.; Cossaro, A.; Pedio, M.; Garcia‐Barriocanal, J.; Castro, G. R.; Davidson, B. A.
<x xml:space="preserve">Abstract</x> Atomic engineering of perovskite films and interfaces is significantly improved by in situ optimization of reflection high‐energy electron diffraction (RHEED) features resulting from surface BO6 octahedral rotations seen during molecular‐beam epitaxy growth. This approach yields Sr‐doped manganite films across the phase diagram with magnetotransport properties that are, for the first time, identical to bulk single crystals. Careful structural analysis of manganite/titanate interfaces shows that cation intermixing and unit cell dilations are eliminated, while BO6 rotations and Jahn‐Teller‐type elongations are nearly completely suppressed at the interface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>